Examination of the Interproximal Wear Mechanism: Facet Morphology and Surface Texture Analysis. (December 2018) - Pokhojaev, A.; Habashi, W.; May, H.; Schulz-Kornas, E.; Shvalb, N.; Sarig, R.
Dentition is considered a dynamic system with forces that directly affect dental treatment stability and success. Understanding the biomechanical forces that influence tooth alignment is essential for both planning and performing dental treatments, as well as for anthropological and evolutionary studies. While there is currently an abundance of research on the mechanics of dental wear at the occlusal surface, the mechanics of interproximal dental wear is largely unexplored. The fretting mechanism, a wear process resulting from small-amplitude cyclic motion of 2 solid contacting surfaces, was refuted as a possible mechanism for occlusal wear but has never been considered for interproximal wear. Therefore, the aim of the current study was to reveal the biomechanical process of the interproximal wear and to explore whether the fretting mechanism could be associated with this process. Premolar teeth with interproximal wear facets were examined by 3-dimensional surface texture analysis using a high-resolution confocal disc-scanning measuring system. The unique texture topography of 3 areas in the proximal surface of each tooth was analyzed by applying 3D dental surface texture analysis. Each area showed unique texture characteristics, presenting statistically significant differences between the inner area of the facet and its margins or the surface outside the facets borders. Based on these results, we concluded that fretting is a key mechanism involved in interproximal wear.